Adjacency Pairsdalam Interaksi Guru Dan Siswa Pada Program English Day Di Sd Internasional Mutiara Persada Yogyakarta - Makasau, Rosmayasinta (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2016)
This study focused on the adjacency pairs in teacher-students interactions in an English Day Program. The aims of this study are to find out the language functions and the types of adjacency pairswhich dominantly occured in teacher students interaction in the English Day program at Mutiara Persada international elementary school. The research addressed a research question: What types of adjacency pairsdominantly occur in teacher-student interaction in the English Day program at Mutiara Persada international Elementary School Yogyakarta? Unlike most other elementary schools in Indonesia, this school has an English Day Program on Saturdays. The participants in this research were the 23 students of grade IV and a non-native English teacher. The analysis results show that the greatest amount of teacher talk in indoor and outdoor category is primarily due to an emphasis on giving information and giving instructions. In contrast, student talk in indoor and outdoor categories are largely in the functions of responding physically and acknowledging. The findings revealed that the types of adjacency pairsfound in teacher student interactions in indooroutdoor category include, among others, giving information /acknowledging, giving instruction, question/ answer, inviting/ accepting, asking and showing attention, greeting, etc. There are more than 10 types of adjacency pairsfound in the current study compared with the 6 types found by the previous researchers. Those types of adjacency pairswill enrich teacher’s strategies in provoking interactions with students in order to foster learning.